2016
DOI: 10.1002/ana.24800
|View full text |Cite
|
Sign up to set email alerts
|

Repeat‐associated non‐AUG translation from antisense CCG repeats in fragile X tremor/ataxia syndrome

Abstract: Objective Repeat associated non-AUG (RAN) translation drives production of toxic proteins from pathogenic repeat sequences in multiple untreatable neurodegenerative disorders. Fragile X-associated tremor/ataxia syndrome (FXTAS) is one such condition, resulting from a CGG trinucleotide repeat expansion in the 5′ leader sequence of the FMR1 gene. RAN proteins from the CGG repeat accumulate in ubiquitinated inclusions in FXTAS patient brains and elicit toxicity. In addition to the CGG repeat, an antisense mRNA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 39 publications
(140 reference statements)
3
70
0
Order By: Relevance
“…This discovery opened the floodgates, and soon evidence accumulated for RAN translation of CAG and other repeats in additional contexts. To date, multiple repeat-encoded proteins that are translated using non-canonical initiation sites have been identified in aggregates in patients with repeat-expansion diseases, and many other repetitive proteins can be generated from RAN translation in vitro (Table 1; (Krans et al, 2016; Todd et al, 2013; Zu et al, 2011, 2013). For example, six RAN proteins, corresponding to all frames of sense and antisense transcripts, are produced from the hexanucleotide expansion found in an intron of C9ORF72, the most common familial cause of ALS and frontotemporal dementia (FTD) (Zu et al, 2013).…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionsmentioning
confidence: 99%
See 4 more Smart Citations
“…This discovery opened the floodgates, and soon evidence accumulated for RAN translation of CAG and other repeats in additional contexts. To date, multiple repeat-encoded proteins that are translated using non-canonical initiation sites have been identified in aggregates in patients with repeat-expansion diseases, and many other repetitive proteins can be generated from RAN translation in vitro (Table 1; (Krans et al, 2016; Todd et al, 2013; Zu et al, 2011, 2013). For example, six RAN proteins, corresponding to all frames of sense and antisense transcripts, are produced from the hexanucleotide expansion found in an intron of C9ORF72, the most common familial cause of ALS and frontotemporal dementia (FTD) (Zu et al, 2013).…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionsmentioning
confidence: 99%
“…However, recent evidence demonstrates that repeat length constitutes a major determinant influencing translation. While repeat length is often positively correlated with the levels of both AUG-initiated and RAN translation (Krans et al, 2016; Krauss et al, 2013; Scoles et al, 2015; Zu et al, 2011, 2013, 2017), RAN translation is only observed from transcripts with pathogenic repeats (Gaspar et al, 2000; Mori et al, 2013a; Todd et al, 2013; Zu et al, 2011, 2013). A similar dependence on pathogenic repeat length has been observed for frameshifting (Saffert et al, 2016).…”
Section: Non-canonical Translation Of Nucleotide Repeat Expansionsmentioning
confidence: 99%
See 3 more Smart Citations